FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN NASABAH DALAM MEMILIH BANK SYARI'AH DI KOTA BANDA ACEH - Sufitrayati, Sufitrayati; Nailufar, Fanny (Fakultas Ekonomi dan Bisnis Islam, 2018)
This study aims to determine the analysis of factors that influence customer decisions in choosing a Syari'ah Bank in Banda Aceh City partially or simultaneously. This study uses 100 customers as samples. The results showed that cultural factors, social factors, personal factors and psychological factors have a significant effect on customer decisions in choosing a Sharia Bank in Banda Aceh City, as evidenced by the results of the research showing the percentage of 81.6% and the remaining 18.4% influenced by other factors beyond the variables studied. Based on the results of multiple linear regression analysis, it can be seen that of the four variables studied, it turns out that the psychological factor variable (X4) has the most dominant influence on the decision of Sharia Bank customers in Banda Aceh, with a coefficient of 0.828, then followed by the cultural factor (X1) with a coefficient value of 0.662, followed by a social factor variable (X2) with a coefficient of 0.549 and followed by a personal factor variable (X3) with a coefficient of 0.110.